Transformaciones del modelo económico y relaciones externas de Cuba: impactos sobre el Caribe - Antonio F. Romero Gómez (Études Caribéennes)
The aim of this article is to gain a better understanding of the relationship between the process of updating Cuba's economic and social model and the changes that have taken place in the country's foreign policy. The main features of the island's recent ties with other Caribbean island nations are analyzed. Emphasis is also placed on elements linked to the re-establishment of diplomatic relations with the United States.